2016
DOI: 10.1186/s13032-016-0031-z
|View full text |Cite
|
Sign up to set email alerts
|

Trauma transfers to a rural level 1 center: a retrospective cohort study

Abstract: BackgroundThe regionalization of trauma care, the Emergency Medical Treatment and Active Labor Act of 1986, the advent of Accountable Care Organizations and bundled payments have brought Level 1 trauma centers (TC) to a new crossroads. By protocol, injured patients are preferentially transferred to designated TCs when a higher level of care is indicated. Trauma transfers frequently come during off hours and may not always appear to be related to injury severity. Based on this observation, we hypothesized patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The air mode of transport likely reflects the distance to trauma centers, as well as the severity of injury. Most children from farms with severe injuries will typically first require stabilization at local hospitals prior to transfer to trauma centers . The data presented indicates that the proportion of children with higher ISS from farm injuries who require rapid transfer to advanced trauma centers either from the field or from a local emergency center is greater than that of children injured at home.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The air mode of transport likely reflects the distance to trauma centers, as well as the severity of injury. Most children from farms with severe injuries will typically first require stabilization at local hospitals prior to transfer to trauma centers . The data presented indicates that the proportion of children with higher ISS from farm injuries who require rapid transfer to advanced trauma centers either from the field or from a local emergency center is greater than that of children injured at home.…”
Section: Discussionmentioning
confidence: 91%
“…Most children from farms with severe injuries will typically first require stabilization at local hospitals prior to transfer to trauma centers. [22][23][24] The data presented indicates that the proportion of children with higher ISS from farm injuries who require rapid transfer to advanced trauma centers either from the field or from a local emergency center is greater than that of children injured at home. Previous studies have demonstrated that the requirement for air transport correlates with worse clinical outcome.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations